PERANCANGAN BASIS DATA UNTUK SISTEM KEARSIPAN PEGAWAI BADAN TENAGA NUKLIR NASIONAL (BATAN) - Harry Dhika; Fitriana Destiawati (Faktor Exacta, 2011)
The research objective is to find out what kind of system used in processing the data archives that exist within the Bureau of Human Resources and what obstacles encountered in implementing such a system. Moreover, the authors hope readers can understand the use of a particular system application filing system. During the study authors found that on Archival Unit BATAN not have a computerized data processing system so that it can assist the work of our employees to become more quickly and effectively. This is because the lack of human resources who know about information systems. After doing some research, the authors conclude that BATAN Archival Unit requires a computerized system so that it can help their employees work. The author tries to create a system of Civil Filing System using Visual Basic programming language.Key Words: system, information, archives